Magahī Rāmāyaṇa : Rāma carita mānasa kā Ma-gahī anuvāda - Siṃha, Indradeva, 1941- (Milane kā patā Rāya Presa, 1982)
Transcreation of Rāmacaritamānasa, Awadhi extended narrative poem on the life and exploits of Rāma (Hindu deity), by Tulasīdāsa, 1532-1623, religious poet.